Consent Searches as a Threat to Procedural Justice and Police Legitimacy: An Analysis of Consent Requests During Traffic Stops. (November 2013) - Gau, Jacinta M.
Consent searches during traffic stops offer police a way to expediently check motorists' vehicles for contraband. Asking drivers for consent to search their vehicles, however, may cause them to feel negatively about the encounter and, consequently, to question officers' motives for pulling them over. The present study analyzes stopped motorists' reactions to consent requests; specifically, consent requests are theorized to damage these individuals' perceptions of procedural justice and, moreover, of the legitimacy of the stop itself. Logistic regression analyses of a nationally representative sample support these hypotheses. Policy implications include the need for judicious use of consent searches, as they appear to be a form of procedural injustice that erodes police legitimacy.